Bibliometric Analysis of Green Marketing in Asia (2000 - 2020) - Muhammad Mujahid Dakwah; Abdurrahman Abdurrahman (Universitas Bumigora, 2023)
Green Marketing (GM) concepts provide suitable solutions for balancing efficiency and environmental concerns. The objective of this paper is to provide an extensive bibliometric literature review on ‘green marketing’ as a term and concept. Articles were located through scopusr database over a period of 20 years (2000 - 2020). The population in question is 1,104 scientific publication titles (9 November 2020). Mendeley software was used to manage and resume the references. We have reviewed this database and attempted to classify articles using VOSviewer software. fourteen clusters were reviewed; the words most frequently occurring in each group were ‘green consumer behavior’, ‘green awareness, 'evnironmental sustainability', 'greenwash' and ‘corporate social responsibility’. This cluster represents the research streams of green marketing.